An Elegant Solution Using Hybrid Power Filter to Improve the Line Current Spectrum of Multiphase PWM Locomotive Rectifiers with Load Unbalance - Kuppa, V.; Wolfs, Peter (Victoria University, 2006)
Locomotive PWM Rectifiers employed in A.C traction systems represent several megawatts of electrical load. Typically they use multiple rectifiers/converters in parallel in order to secure high power ratings and high frequency operation. The rectifiers are supplied from a single-phase A.C. traction transformer with multiple secondaries of high leakage inductance. The switching instants of the PWM rectifiers are phase shifted and interlaced in order to achieve high ripple current cancellation, assuming that the converter loads are balanced. This would ensure the rectifiers to provide better harmonic performance and also redundancy of operation with multiple units in operation. However, in practice, rectifiers may be closely coupled to a traction inverter supplying an axle or a group of axles and the real power developed will depend upon the traction conditions. Creep and slip can give rise to variations in power and perfect power balance at the rectifiers is an improbable proposition.There is high degree of interest to examine the possibility locomotive systems that degrade gracefully with equipment failure. Failure of one traction inverter would lead to load unbalance for the rectifier modules. Or sometimes, partial failures may result in unbalanced operation which can cause reduced ripple current cancellation and generate switching frequency harmonic current components. This may adversely impact the signalling systems and/or result in over voltage effects due to resonance in the overhead supply system. This paper examines a 4 MW locomotive with three rectifier modules and a device switching frequency of 900 Hz. This results in a 5400 Hz ripple frequency in the mains current. And this paper will consider what may be the most frequently occurring case; that of loss of load in one traction motor due to wheel slip. Current ripple cancellation is partially lost in this case and lower frequency current components can be produced. Traditionally, number of solutions has been employed in the industry like passive filters, active filters etc., for this type of a problem. However, this paper explores an elegant, attractive and economical solution of using hybrid filters in order to achieve a level of acceptable satisfactory harmonic performance and thereby improving the power quality of the rail systems.